2015
DOI: 10.3390/su70810684
|View full text |Cite
|
Sign up to set email alerts
|

Investment Strategy of Emission-Reduction Technology in a Supply Chain

Abstract: Greenhouse gas emissions have serious impacts on the natural environment. Therefore, the restrictions imposed on carbon emission force enterprises to take carbon emission into consideration when making production decisions. In this paper, in the context of allowing emission trading and investment of emission reduction technology, models were presented for a two-stage supply chain to analyze the optimal investment and pricing decisions. The results indicate that manufacturer's endurance capacity of reduction di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…This implies that = −(1/ )ln(1 − / ). This relation is analogous to the relation considered by Lou et al [9]. The fraction of reduction is 0, when = 0, and tends to when tends to infinity.…”
Section: Model Parameterssupporting
confidence: 57%
See 2 more Smart Citations
“…This implies that = −(1/ )ln(1 − / ). This relation is analogous to the relation considered by Lou et al [9]. The fraction of reduction is 0, when = 0, and tends to when tends to infinity.…”
Section: Model Parameterssupporting
confidence: 57%
“…The fraction of reduction is 0, when = 0, and tends to when tends to infinity. Lou et al [9] took = 1. The parameter reflects the efficiency of greener technology in reducing emission.…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni et al [18] found that socially responsible or environmental performance is highest in the cooperative supply chain, where the supplier and the manufacturer jointly maximize the supply chain profit, mainly because the double marginalization problem is eliminated. Lou et al [19] also examined three supply chain configurations and found that cooperative supply chain in which the manufacturer and the retailer act as a single firm and the supply chain coordinated by a revenue sharing contract invest in emission reduction more than the decentralized supply chain. Klassen and Vachon [20] empirically showed that an increased collaboration in the supply chain helps the firms invest more in environmental programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, EURO 6 was instated in 2014 and imposed in 2015. The stricter emission regulations induce technological competition and innovation [10] in the HDDE market, and in this situation, HDDE companies have to control the production of past-generation and new-generation HDDEs for the management of inventory and efficient operation of limited production facilities.…”
Section: Introductionmentioning
confidence: 99%